Maternal Self-Construal, Maternal Socialization of Emotions and Child Emotion Regulation in a Sample of Romanian Mother-Toddler Dyads - Benga, Oana; Susa-Erdogan, Georgiana; Friedlmeier, Wolfgang; Corapci, Feyza; Romonti, Mara (Frontiers in Psychology, 2019)
Over the recent years, there is growing recognition of the social and cultural regulatory processes that act upon individual emotions. The adult-to-child social regulation of emotion is even more relevant, given the development of child self-regulatory abilities during early years. Although it is acknowledged that parental regulatory attempts to their children’s emotional expressions are influenced by cultural models, relatively little is known about the specific relationship between parental cultural models and socialization practices that foster emotion self-regulation, particularly in the case of toddlers. Therefore, in the present study, our first aim was to examine, in a Romanian sample of mother-toddler dyads, the relationships between maternal cultural model of self and maternal regulatory attempts targeting toddlers’ emotions during a delay of gratification task, while controlling for maternal perceptions of child individual characteristics, namely temperament. The second aim was to analyze, within the delay of gratification task, the relations between maternal regulatory attempts, child regulatory strategies and child affect expression, as the outcome of emotion regulation. Results showed that mothers scored higher for Independence as compared to Interdependence dimensions of self-construal. Also, the multidimensional analysis of self-construal revealed that Autonomy/Assertiveness scores were significantly higher than Relational Interdependent scores. Moreover, different dimensions of Independence predicted different maternal regulatory strategies employed during the delay of gratification task. This pattern of results suggests that maternal representations of an independent self, evidenced in our sample, are reflected in regulatory practices, aimed to develop primary control in the toddler. Moreover, our data revealed several significant associations between maternal regulatory strategies and child regulatory strategies expressed during the delay of gratification task. Finally, we demonstrated that child self-regulation mediated the relation between maternal regulatory attempts and child expression of affect during this task.